Broadcasting Organization in the Context of Creative Economics and Management Innovation - uro Horvat; Marinko Kovačić; Ana Krajnović (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The transformation of the modern economic system is more than obvious and our main objective is to point out the need for the articulation of new organizational forms. In this paper, we use the results of empirical studies published in the literature and theoretical elaboration by using inductive/deductive methods. We believe that a new organization must correspond to human nature, which is based on selfaffirmation in the world of labor in which the creativity, imagination, play and cooperation are among the key factors.
Keywords: L1; 330; broadcasting organization; innovation; structure; cooperation; knowledge